Kelayakan Jaringan Transportasi Sungai Kabupaten Mimika - Arief Hidayat; Hijriah Hijriah; Noni Oktiana Setiowati (Fakultas Teknik Universitas Bosowa, 2023)
Mimika Regency is a coastal area with great potential with rivers. The river is one of the critical lines of the economy, a source of water and employment for the Mimika people. In the development of river transportation, technical criteria are needed to assess whether the river transportation network in Mimika Regency is feasible or not. The analysis used is bathymetric, an analysis of the relationships between river transportation variables and the origin and destination of movement, swot analysis, capacity of river transportation areas, level of utilization of river transportation capacity, and loading and unloading requirements in river transportation. From the analysis and technical aspects, the development of the river is very feasible for the development of the transportation network in Mimika Regency.